AETHIOLOGIC FACTORS IN CHRONIC PANCREATITIS - Ali Reşit BEYLER; Abdulkadir DÖKMECİ; Ahmet Teoman ERTEN; Erol KESİM; Murat PALABIYIKOĞLU; Nihat SİPAHİ; Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-